Unschärfe in der Erziehungswissenschaft Bilanzierung einer Wissensform - Gallmann, Martin Eugen (Verlag Barbara Budrich, 2018)
Fuzzy knowledge is not (only) a problem, but a capital of educational science. Based on this thesis, the author examines the educational discourse on the basis of the journal for educational science. In contrast to pedagogical certainties and calculabilities, the logical structure of fuzzy knowledge has a grammar that goes beyond simple truth values. In the form of a (metatheoretical) typology, different theoretical approaches to the topic of imprecise knowledge are systematized and exemplified with reference to concrete pedagogical problems.